Identification of genes required for the spontaneous repair of partial-thickness cartilage defects in immature rats. (3rd May 2016) - Ikegawa, Naoshi; Sasho, Takahisa; Yamaguchi, Satoshi; Saito, Masahiko; Akagi, Ryuichiro; Muramatsu, Yuta; Akatsu, Yorikazu; Fukawa, Taisuke; Nakagawa, Koichi; Nakajima, Arata; Suzuki, Takane; Takahashi, Kazuhisa
ABSTRACT: Purpose : Our previous study showed that partial-thickness articular cartilage defects (PTCDs) created in immature rats spontaneously healed to resemble normal hyaline cartilage, but that of mature rats did not. To identify molecules involved in the spontaneous cartilage repair observed in this model, gene expression was compared between PTCD and sham-operated cartilage of immature and mature rats. Materials and Methods : Six sets of gene comparisons were made at 12, 24, and 48 hours after the creation of PTCDs in immature and mature rats using microarrays. All the genes upregulated in immature cartilage at 12 hours were selected for further analysis if their expression pattern was not irregular such that diminished at 24 hours and re-upregulated at 48 hours. Relationships among genes selected through the above steps were analyzed using Ingenuity Pathway Analysis (IPA) software. After deriving networks, important molecules were further narrowed down by location within a network. Genes were regarded as central if they had relationships with more than 10 molecules in a network. Protein localization in tissues was confirmed by immunohistochemistry. Results : Five networks were identified. Their functional annotations were gene expression, cell cycle, growth and proliferation, and cell signaling. Transforming growth factor-beta (TGF-β) was centrally located in the network with the highest IPA score and mothers against decapentaplegic homolog-3 (Smad3) were centrally located in the second highest ranking network. Phosphorylated Smad3 was detected in the nuclei of chondrocytes in immature cartilage. Conclusions : Our data suggest the possible importance of Smad3 in the TGF-β signaling in the spontaneous healing of PTCDs in immature rats.